2014
DOI: 10.1111/bcpt.12330
|View full text |Cite
|
Sign up to set email alerts
|

Altered Frequency Distribution in the Electroencephalogram is Correlated to the Analgesic Effect of Remifentanil

Abstract: Opioids alter resting state brain oscillations by multiple and complex factors, which are still to be elucidated. To increase our knowledge, multi-channel electroencephalography (EEG) was subjected to multivariate pattern analysis (MVPA), to identify the most descriptive frequency bands and scalp locations altered by remifentanil in healthy volunteers. Sixty-two channels of resting EEG followed by independent measures of pain scores to heat and bone pain were recorded in 21 healthy males before and during remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, we wanted to investigate a design comparable for future simultaneous electroencephalography (EEG) recordings of evoked potentials. Studies suggested EEG alterations to be correlated with the analgesic effect , and a combination of information from EEG and MRI provides both high temporal and spatial resolution. Even though habituation was present, we showed activation of the ‘pain matrix’.…”
Section: Discussionmentioning
confidence: 99%
“…However, we wanted to investigate a design comparable for future simultaneous electroencephalography (EEG) recordings of evoked potentials. Studies suggested EEG alterations to be correlated with the analgesic effect , and a combination of information from EEG and MRI provides both high temporal and spatial resolution. Even though habituation was present, we showed activation of the ‘pain matrix’.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic neurogenic pain presents higher spectral power over the frequency range of 2–25 Hz (Bromm and Lorenz, ; Sarnthein et al , ). Besides, analgesic drugs can also trigger particular EEG alterations in the brain (Graversen et al , ; Hartley et al , ), and the pain‐relieving effect varies according to individual baseline brain activity (Jensen et al , ). Furthermore, it has been found that the anticipation of pain can also activate certain brain areas and significantly enhance EEG signals, even without a physical pain stimulus (Villemure and Bushnell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypnosis, immobility and adequate analgesia are needed for most surgical procedures. Since remifentanil and dexmedetomidine both have proven analgesic as well as hypnotic effects, and both alter EEG parameters [29,38,39], the influence of each aforementioned property, however, can only be estimated.…”
Section: Discussionmentioning
confidence: 99%